Effects of Coriolis force, vorticity and divergence on nonlinear energy conversions during different phases of July 1979 monsoon (MAUSAM, 1997)
ABSTRACT. Kinetic energy (KE) of the rotational and divergent flows and the nonlinear energy conversion between them due to the action of Coriolis force, divergence and vorticity, partition) further into stationary and transient motions are computed in the Fourier spectral domain during different phases of July 1979 monsoon over the latitudinal belt 10° S - 30° at 850 and 200 hPa and studied. It is found that nonlinear divergent to rotational KE exchange due to the action of Coriolis force is the primary contributor for all categories of stationary and transient waves at both the levels over tropics. Our results indicate that in the transient scale dynamics the wave-wave interaction plays a dominant role at 850 hPa. Divergent to rotational KE conversion by zonal-wave interaction due to divergence and wave-wave interaction due to Coriolis force are identified as important mechanisms for maintenance of rotational stationary planetary and transient synoptic scale waves respectively at 200 hPa. It is inferred that nonlinear energy conversions due to Coriolis force and vorticity oppose each other at 200 hPa. The results support that the energy conversion phenomenon may not be entirely barotropic. The importance of ageostrophic effect at different stages of monsoon activities is also shown.